Carcass Composition of Crossbred and Straightbred Lambs Finished on a High Concentrate Diet - Malik, R.C.; Mohammed, S.A.; Razzaque, M.A.; Al-Khozam, N.M. (Pakistan Journal of Nutrition, 2009)
The body measurements and carcass composition of 35 Naeemi x Border Leicester Merino (NaeemixBLM) crossbred and 9 Naeemi straightbred lambs were investigated. The Naeemi lambs were, on average, 2 kg heavier and had the Body Conditioning Scores (BCS) that were 0.78 points lower and body lengths that were 10.2 cm shorter than the crossbred lambs. There were no significant differences between the genetic groups for (GR) or (BT) but crossbred lambs had significantly more kidney fat. They also had 5.5% higher dressing percentages and 14% higher carcass yields than the Naeemi lambs. Carcass moisture and protein were 6.3 and 1.6% higher and fat was 7.8% lower in the whole carcasses of the Naeemi lambs than in those of the crossbred lambs. It is concluded that the Naeemi x BLM lambs produce heavier carcasses but also accumulate more carcass fat than straight Naeemi lambs.